2007
DOI: 10.1002/ibd.20068
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatment may reduce the need for healthcare in patients with Crohnʼs disease

Abstract: A significant drop in healthcare utilization after psychological treatment demonstrates a clear benefit of this additional therapy. This is important, since the study failed to demonstrate significant changes in the psychosocial status or somatic course of study patients. Clinical and psychological factors influencing these outcomes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…However, in a follow-up study of this cohort, they found in multivariate analysis that steroid intake and depression predicted worse disease outcomes. In the high utilizers of health care, a signifi cant drop in healthcare utilization was noted in those treated vs. not for their depression ( 118 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…However, in a follow-up study of this cohort, they found in multivariate analysis that steroid intake and depression predicted worse disease outcomes. In the high utilizers of health care, a signifi cant drop in healthcare utilization was noted in those treated vs. not for their depression ( 118 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…[44,58]. Many of the above studies have found long lasting effects from brief therapeutic interventions which may contribute to reduced health care utilization and costs and decreased productivity loss in managing IBD, for example reduction of outpatient attendances, sick-leave and hospital days [6,20,31,47,51,55,58]. Yet, some have found only a short term benefit with a diminished positive effect of therapy over time [57,60].…”
Section: Discussionmentioning
confidence: 99%
“…Forty CD patients who underwent 20 hours of psychodynamic psychotherapy without the use of a manual, and 10 relaxation treatment sessions over a 1 year period, showed a significant higher decrease in hospital and sick-leave days compared to 24 controls [51]. No significant effects on psychological indices were found, but the treatment group reported few psychological symptoms at baseline; patients who wanted psychological treatment or who had psychiatric co morbidity were excluded.…”
Section: Psychodynamic Therapymentioning
confidence: 95%
“…Thus, our results, in conjunction with prior studies in the literature, suggest a potential need for routine screening for psychiatric co-morbidity in IBD patients. In addition, there is continued need for research on interventions addressing depression and anxiety in IBD patients as the literature so far has been limited and conflicting 22,48,49 . Such interventions may improve mood and health-related quality of life as well as natural history of disease and IBD-related healthcare costs.…”
Section: Discussionmentioning
confidence: 99%